Escribir para aprender: Mi experiencia en un programa MBA - Marcos Gallacher (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2019)
– This paper analyzes the potential of written assignments for the learning process of MBA students. Some of the challenges faced by MBA programs are discussed, and a contrast is made between the "passive" and "active" learning approaches. The paper details some of the difficulties students have in completing a written assignment. The author's experience in directing student monographs in the areas of (a) firm limits, (b) human resources and (c) firm organization is discussed. It is argued that many of the completed monographs have not only resulted in intellectual growth of the students, but have also produces valuable information on economics of organizations.
Keywords: D22; D23; M20; 330; Betriebswirtschaftsstudium; Wissenschaftliches Arbeiten; Lernprozess